Escola pública e discurso meritocrático: propostas da reforma do ensino médio e expectativas dos estudantes (Educação e Pesquisa, 2024)
This article discusses the reform proposals for secondary education, reflecting on the extent to which some of the proposed contents and practices converge with individualistic and meritocratic concepts and discourses already present in the public school environment, but now reinforced. Based on a broad set of surveys conducted between 2019 and 2022, it seeks to capture the meritocratic perceptions of public school students from Ceará. Reflexive data analysis allowed us to identify a considerable expectation among high school students for an educational and future life that provides stability and desirable social conditions. Such expectation, however, goes hand in hand with a mass adherence to meritocratic and individualistic discourse in general, with little reflection on social conditioning factors. The reports and data indicate that school agents—teachers and classmates—are significant players in the process of constructing this view. However, one must consider a possible mismatch between young people’s expectations and the educational reality provided by this new high school. At a time when higher education is expanding and knowledge-based economic dynamics are intensifying, schools play an increasingly key role in ensuring an adequate, complete education as to not produce even greater educational gaps between different social groups, especially in Brazil’s already serious context of social and educational inequalities.